2013
DOI: 10.1503/cjs.029511
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of complications after intramedullary fixation for displaced midshaft clavicle fractures

Abstract: Background:The number of displaced midshaft clavicle fractures treated surgically is increasing, and open reduction and intramedullary fixation is an emerging surgical treatment option. The study quality and scientific levels of published evidence in which possible complications of this treatment are presented vary greatly. Methods:We performed systematic computer-based searches of EMBASE and PubMed/MEDLINE. Studies included for review reported complications after intramedullary fixation alone or in comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 40 publications
0
22
0
4
Order By: Relevance
“…24,31,32,34,35 Smekal et al reported that 23% of their patients had medial nail protrusion. 24 Medial protrusion of the nail, though evident in most cases in our series, was not significant enough to necessitate removal of the hardware.…”
Section: Discussionmentioning
confidence: 99%
“…24,31,32,34,35 Smekal et al reported that 23% of their patients had medial nail protrusion. 24 Medial protrusion of the nail, though evident in most cases in our series, was not significant enough to necessitate removal of the hardware.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2011, a few review papers and randomized-control trials have been recently published and may be of interest, including Kulshrestha, Mirzatolooei, Ban, Virtanen, Wijdicks, Liu, Formaini, and Xu (Kulshrestha et al, 2011;Mirzatolooei, 2011;Ban et al, 2012;Virtanen et al, 2012b;Wijdicks et al, 2012bWijdicks et al, , 2013Liu et al, 2013;Formaini et al, 2013;Xu et al, 2013;Xu et al, 2014). Since 2011, a few review papers and randomized-control trials have been recently published and may be of interest, including Kulshrestha, Mirzatolooei, Ban, Virtanen, Wijdicks, Liu, Formaini, and Xu (Kulshrestha et al, 2011;Mirzatolooei, 2011;Ban et al, 2012;Virtanen et al, 2012b;Wijdicks et al, 2012bWijdicks et al, , 2013Liu et al, 2013;Formaini et al, 2013;Xu et al, 2013;Xu et al, 2014).…”
Section: Sources Of Further Information and Advicementioning
confidence: 99%
“…12,16 Intramedullary fixation has been considered to be a more difficult surgical technique to master with a steep learning curve as compared with more traditional plating. 12,16 Intramedullary fixation has been considered to be a more difficult surgical technique to master with a steep learning curve as compared with more traditional plating.…”
Section: Intramedullary Fixationmentioning
confidence: 99%